Addiction Treatment as Prison Governance: A Critical Discourse Analysis of Methadone Delivery in Kyrgyz Prisons. (March 2022) - Azbel, Lyu; Bromberg, Daniel J.; Dvoryak, Sergii; Altice, Frederick L.
Methadone treatment is prescribed by evidence-based medicine as the most effective tool for the treatment of opioid addiction. Its implementation into high-need prison settings worldwide has been met with challenges, particularly in Eastern Europe and Central Asia where the opioid epidemic continues to expand. To address these impasses to intervention translation, we turn to post-structural approaches to policy analysis. These approaches open space for (re)thinking the ways that translated interventions emerge locally, by treating policy texts as social practices that make interventions in specific, sometimes unexpected, ways. We leverage Carol Bacchi's post-structuralist analytic framework to interrogate how the object of methadone is constituted in Kyrgyz prisons through an analysis of the national legislative document, the "Government Program, " which provides the legislative basis for opioid addiction treatment administration in the Kyrgyz Republic. Rather than the medicalized methadone for the treatment of opioid use disorder, contained in the distinct objectivization of methadone emerging from this policy text, is the previously unexamined assumption that methadone is a particular type of governance. We describe a methadone object tied up with the shifting social structures that govern Kyrgyz prisons, divided between formal (state-run) and informal (prisoner-run) governance. In Kyrgyz prisons, where opioid policy discourse produces a divide between formal and informal governance, methadone emerges as a tool of the formal prison administration to regain control of the prisons from the practices of prisoner subculture. Although this study takes the Kyrgyz case as an example, the enactment of methadone as formal governance is likely to resonate throughout Eastern Europe and Central Asia, where there is a strong legacy of self-governing prisons. We conclude with a call for global health policymakers to consider how opioid addiction treatment is constituted within local governing relations, in ways that may depart sharply from the evidence base.